Molecular Signatures of Biogeochemical Transformations in Dissolved Organic Matter from Ten World Rivers - Riedel, Thomas; Zark, Maren; Vähätalo, Anssi V.; Niggemann, Jutta; Spencer, Robert G. M.; Hernes, Peter J.; Dittmar, Thorsten (Frontiers in Earth Science, 2016)
Rivers carry large amounts of dissolved organic matter (DOM) to the oceans thereby connecting terrestrial and marine element cycles. Photo-degradation in conjunction with microbial turnover is considered a major pathway by which terrigenous DOM is decomposed. To reveal globally relevant patterns behind this process, we performed photo-degradation experiments and year-long bio-assays on DOM from ten of the largest world rivers that collectively account for more than one-third of the fresh water discharge to the global ocean. We furthermore tested the hypothesis that the terrigenous component in deep ocean DOM may be far higher than biomarker studies suggest, because of the selective photochemical destruction of characteristic biomolecules from vascular plants. DOM was molecularly characterized by a combination of non-targeted ultrahigh-resolution mass spectrometry and quantitative molecular tracer analyses. We show that the reactivity of DOM is globally related to broad catchment properties. Basins that are dominated by forest and grassland export more photo-degradable DOM than other rivers. Chromophoric compounds are mainly vascular plant-derived polyphenols, and partially carry a pyrogenic signature from vegetation fires. These forest and grassland dominated rivers lost up to 50% of dissolved organic carbon (DOC) during irradiation, and up to 85% of DOC was lost in total if subsequently bio-incubated for one year. Basins covered by cropland, on the other hand, export DOM with a higher proportion of photo-resistant and bio-available DOM which is enriched in nitrogen. In these rivers, 30% or less of DOC was photodegraded. Consistent with previous studies, we found that riverine DOM resembled marine DOM in its broad molecular composition after extensive degradation, mainly due to almost complete removal of aromatics. More detailed molecular fingerprinting analysis (based on the relative abundance of >4000 DOM molecular formulae), however, revealed clear differences between degraded riverine and deep-sea DOM (molecular Bray-Curtis dissimilarity of ~50%). None of our experimental treatments enhanced the molecular similarity between the rivers and the deep ocean. We conclude that terrigenous DOM retains a specific molecular signature during photo-degradation on much longer time scales than previously assumed and that substantial, thus far unknown, molecular transformations occur prior to downward convection into the deep oceanic basins.